VALIDITAS LEMBAR KEGIATAN PESERTA DIDIK BERBASIS GUIDED INQUIRY STRATEGI READING INFUSION PADA SUB MATERI TEKANAN ZAT CAIR UNTUK MENINGKATKAN LITERASI SAINS SISWA SMP - Restiana Mi'rojul Laili; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research was conducted with the aim of describing the validity of the student activity sheet based on Guided Inquiry Reading Infusion strategy. This study uses a 4-D development model (Define, Design, Develop, Disseminate), but this research is limited only to the Develop stage. Collecting research data using a questionnaire to determine the validity of the student worksheets. The validated student worksheets are student worksheet 1, student worksheet 2, and student worksheet 3. The results showed the analysis of the value of validity value on the aspects of the Dikdactic requirements of 85.27%, 87.08%, and 88.20%, aspects of the constructive requirements of 89.27%, 87.79%, and 88,16% and on the technical requirements of 85.00%, 88.33%, and 87.22%. The conclusion of this research is Guided Inquiry worksheets based on Reading Infusion strategies on the sub-material of liquid pressure to improve students' scientific literacy are declared feasible and valid.